Collation of Diverse Ontology Tools - Kanakam, Prathyusha; Edarapalli, Raghu Varma; Hussain, S Mahaboob (International Journal of Computer Sciences and Engineering, 2019)
Internet is the huge repository to provide a way to obtain the web documents in these recent years. Most of these documents are in a human understandable format that provides a bridge to ingress services from the web. These documents provide knowledge to retrieve information from the web. Information retrieval systems fail in providing a specific format for this knowledge representation. By considering all these criteria, Web 3.0 has stepped ahead to web entail peculiar format to obtain information from web documents called ontologies. Ontology is a knowledge-based conceptualization system that consists of concepts, relations and their properties that provides a semantic relationship between the concepts used for a specific domain. Diverse tools are implemented and introduced in the market to develop these ontologies in order to serve a particular purpose. This paper projects the workflow steps of ontology editors and shows the study of different ontology developments tools along with their comparison to one another.